Analisis Kesulitan Belajar Siswa dalam Mata Pelajaran IPA dan Upaya Penanganannya di MTs N 1 Kepulauan Sula - Ipa, Rohani (Global Education Journal, 2023)
This study aims to identify and analyze students' learning difficulties in the subject of Natural Sciences (IPA) at MTsN 1 Kepulauan Sula and the measures to address them. Employing a qualitative approach with a descriptive case study method, data were collected through participant observation, in-depth interviews, and document analysis over eight weeks. The findings indicate that students struggle with understanding abstract concepts such as force, motion, energy, and atomic structure due to insufficient teaching aids and practical exercises. Limited resources and facilities, such as inadequately equipped laboratories and restricted access to information and communication technology (ICT), also hinder the teaching and learning process. Low student motivation, varying levels of academic ability among students, and inadequate parental involvement in home learning are additional factors affecting learning difficulties. Proposed measures include enhancing teaching quality through teacher training, utilizing local resources, and strategies to boost student motivation. Differentiated learning approaches to address varying academic abilities and increased parental involvement are also recommended. These findings provide insights into the challenges of teaching IPA in remote areas and recommend developing educational policies better suited to local contexts.